Sensitivity and Specificity of C-Reactive Protein Against Blood Culture in Patients with Neonatal Sepsis - A Hospital-Based Study - Deepak Kumar; Mashal Khan; Mehmood Shaikh; Muhammad Hanif; Wajid Hussain (Liaquat National Journal of Primary Care, 2024)
Background: Neonatal septicemia is one of the primary causes of disease and death in low-income countries which makes early diagnosis an important factor to prevent microbial resistance and initiate antibiotic therapy. C-reactive protein is an essential biological indicator that might play an important role in the early detection of neonatal sepsis. Objective: The present study was conducted to determine the sensitivity and specificity of CRP against blood culture in the identification of neonatal sepsis. Methods: This study was carried out on 416 neonates identified with sepsis at the NICU and SICU of the National Institute of Child Health, Karachi, Pakistan for a span of 06 months from April 2022 to September 2022. The first blood sample for the evaluation of CRP and blood culture was drawn at the time of admission. The second sample of CRP and blood culture was drawn 72 hours after the first blood collection. The sensitivity and specificity of CRP were calculated on both occasions. Results: Of the total 416 neonates, 165(39.6 %) patients’ blood culture was positive and in 273 (65.9%) patients CRP was positive. The validation study of CRP in the diagnosis of neonatal septicemia reported sensitivity, specificity, positive predictive value, and negative predictive value to be 87.1%, 45.9%, 52.6%, and 83.7% 72 hours after the admission in comparison to 80.6%, 44.2%, 48.7%, and 77.6% at the time of admission. Conclusion: The high specificity and sensitivity of CRP against blood culture make it an important diagnostic modality that might play a helpful role in the diagnosis of neonatal sepsis.